Globalisation, Trade Openness and Foreign Direct Investment in Romania - Dima, Stela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The paper analyses the trend of globalisation, trade openness and foreign direct investments (FDI) in Romania and the link between them in the last 25 years. Data from UNCTAD, World Bank and KOF globalisation index were used in econometrical models testing the link between globalisation, trade openness and foreign direct investment. A strong positive and statistical validated link is found between globalisation and FDI, between trade openness and FDI, and between FDI and globalisation. In the context of Romanian economy, these three phenomena are interrelated and each of them is acting to potentiate the effect of the other. Moreover, a multivariate regression analysis emphasized the dependency between globalisation index and foreign direct investment, trade openness and market capitalisation. These results can be taken into account when national policies aiming to attract FDI and stimulating export-import activities are designed.